Given the system of equations.
4x+y=8
6x-9y=12
Which of the options represents the resulting equation after an equivalent expression for y is substituted into the second equation?

6x - 9(4x - 8) = 12
4x + 4x - 8 = 8
6(4x - 8) - 9y = 12
6x - 9(-4x + 8) = 12

Respuesta :

Answer:

72 and 8÷

Step-by-step explanation:

Answer:

Choice D which is 6x - 9(-4x + 8) = 12

Step-by-step explanation:

The first equation solves to y = -4x+8 when you subtract 4x from both sides. This to undo the addition of 4x done to y.

Then you replace every copy of "y" in the second equation with (-4x+8). The parenthesis is important so that you multiply properly

We go from 6x - 9y = 12 to 6x - 9( -4x+8 ) = 12